Disease-modifying effects of a novel T-type calcium channel antagonist, Z944, in a model of temporal lobe epilepsy. (November 2019) - Casillas-Espinosa, Pablo M.; Shultz, Sandy R.; Braine, Emma L.; Jones, Nigel C.; Snutch, Terrance P.; Powell, Kim L.; O'Brien, Terence J.
Graphical abstract: Highlights: Z944 treatment after KA-induced post-SE inhibits the development of epilepsy. Z944 treatment after KA-induced post-SE reduces comorbid depressive-like behavior and cognitive impairment. Targeting T-type Ca 2+ channels may be a disease-modifying treatment for TLE. Abstract: We evaluated whether pharmacologically targeting T-type Ca 2+ channels with Z944, a potent and selective antagonist, has disease-modifying effects in a model of temporal lobe epilepsy (TLE) that exhibits spontaneous recurrent seizures, and manifests behavioral and cognitive comorbidities commonly experienced by patients with this condition. Wistar rats underwent implantation of EEG electrodes and one week later 4 h of kainic acid-induced status epilepticus (SE). Animals were randomly assigned to one of 5 different groups: post-SE + Z944 (60 mg/kg/day, n = 8); post-SE + levetiracetam (200 mg/kg/day, n = 9); post-SE + vehicle (n = 8); sham + vehicle (n = 6) or sham + Z944 (60 mg/kg/day, n = 6). Treatments were delivered by continuous subcutaneous infusion for four weeks during which time continuous video-EEG was acquired. Four weeks after completion of treatment, the animals had two further weeks of continuous video-EEG monitoring to evaluate the effects of the different treatments. Behavioral tests were performed to evaluate anxiety, depression, and cognition. On the video-EEG recordings four-week post-treatment, the Z944 group manifest reduced number of seizures (0.01 ± 0.01seizures/day) compared to vehicle (0.8 ± 0.1) and levetiracetam (0.5 ± 0.1) treated animals ( p  < 0.0001). Post-SE+ vehicle rats showed elevated depressive-like behavior, and deficits in spatial learning and memory compared to sham+vehicle rats, and these behavioral deficits were significantly improved in post-SE rats treated with Z944 ( p  < 0.05, for all comparisons). The results of this study show that treatment with Z944 has a disease-modifying effects in the post-SE model of TLE, reducing seizures as well as comorbid depressive-like behavior and cognitive impairment. This indicates that pharmacologically targeting T-type Ca 2+ channels may be an effective disease-modifying treatment for temporal lobe epilepsy.